Post-buckling analysis of rectangular plates comprising Functionally Graded Strips in thermal environments. (15th January 2015) - Ovesy, H.R.; Ghannadpour, S.A.M.; Nassirnia, M.
Abstract: Description is given of a semi-analytical finite strip method for analysing the post-buckling behaviour of functionally graded rectangular plates in thermal environments where plates are under uniform, tent-like or nonlinear temperature change across the thickness. The material properties are assumed to vary through the thickness according to the power law. The formulations are based on the classical plate theory and the concept of the principle of the minimum potential energy. The Newton–Raphson method is used to solve the equilibrium equations. A range of applications are described and the numerical results are compared to the available results, wherever possible.